The Effect Of Perceptions Of Service Quality And Customer Satisfaction On Goride Customer Loyalty - Puti Zalfa Alifah; Ika Apriati Widya Puteri (CAKRAWALA : Management Science Journal, 2026)
Customer loyalty to GoRide in East Jakarta is still relatively low. This study aims to determine the effect of perceived service quality and customer satisfaction on GoRide customer loyalty. The study used a quantitative approach with a non-experimental design and purposive sampling technique. The research subjects were 150 GoRide users who had worked and used the service for at least six months. The instruments used were the Customer Loyalty Scale, Service Quality Scale, and Customer Satisfaction Scale. Data were analyzed using multiple linear regression. The results showed that perceived service quality and customer satisfaction had a significant influence on customer loyalty, with significance values of 0.000 and 0.002 (p < 0.05). This indicates that the higher the perception of service quality and customer satisfaction, the higher the customer loyalty to GoRide.